Development of Personalized Learning Student Worksheets to Practice Inquiry Skills - Triwulandari, Syane; Sumaryoto, Sumaryoto; Leonard, Leonard; Setiono, Setiono (BIOEDUSCIENCE, 2024)
Background: Personalized learning must be based on exploring students' traits, including learning styles. Knowledge of student learning styles will make it easier to design learning, including practicing inquiry skills. Inquiry skills are abilities that all students need to have. Inquiry skills must be trained through habituation, especially through practical learning. Many Student Worksheets (LKM) practice inquiry skills, but they do not accommodate each student's learning style. Method: Development of personalized learning LKM to train inquiry skills using the Borg and Gall development research model. Results: Initial data was taken through interviews and learning style tests. The results of the learning style test show that 35.72% of students have a visual learning style, 25% auditory, and 39.28% kinesthetic. The next stage is to develop visual, auditory, and kinesthetic LKM products on the characteristics of leaves as quite complex material. The products developed are then evaluated through validation by material and inquiry experts, language experts, and development experts. Product improvements are made based on comments and suggestions from validators. The three LKM products were tested for suitability by students as product users. The feasibility score for the visual type of personalized learning LKM was 89%, the auditory type of personalized learning LKM was 90%, and the kinesthetic type of personalized learning LKM was 92%. The results of the effectiveness test of the three products show an increase in students' inquiry skills in the medium category. Conclusion: The three LKM personalized learning products fall into the feasible and usable category.